Release of cisplatin from bioinert templates in mixture with hydroxyapatite - V.K. Krut’ko; L.Yu. Maslova; V.A. Suchok; O.N. Musskaya; A.I. Kulak (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
The dynamics of cisplatin release and its mixture with hydroxyapatite from bioinert templates based on carbon felt and polyethylene were studied. Changing the polyethylene and carbon felt layer ratio in the templates influenced the volumetric concentration of cisplatin and the duration of its release. The diffusion of cisplatin from the samples was limited by the number of polyethylene layers. After crystallization at 800°C, the phase composition of hydroxyapatite-α is 65% hydroxyapatite and 35% α-tricalcium phosphate, and hydroxyapatite-αβ consists of 50% hydroxyapatite, 35% α- and 15% β-tricalcium phosphate. Long-term (44 days) release was observed in templates with 2-3 layers of carbon felt and 3-4 layers of polyethylene, and it was slowed when using mixtures with hydroxyapatite (58 days). The appending of hydroxyapatite/cisplatin mixtures into the template with varying amounts of hydroxyapatite phases and α-/β-tricalcium phosphates slowed the release of cisplatin by 14 days, totaling 58 days, due to the sorption and/or binding of cisplatin to calcium phosphates.